Identifikasi Penyebab Cacat Pada Hasil Pengelasan Dengan Image Processing Menggunakan Metode Yolo - Khumaidi, Agus; Pradana, Rizal Lucky (Jurnal Teknik Elektro dan Komputer TRIAC, 2022)
In everyday life, of course, we often see iron or metal objects that are connected to each other. The joining of these two metals is known as welding. Incomplete welding can cause defects in the welding results, the occurrence of electrode buildup, excessive spatter, and porosity that occurs in the metal plate. Visual Inspection is one of the Non Distructive Test (NDT) methods for the process of testing the welding results. This process is still using the manual method, namely with human eyesight, so the test results are still subjective. The author has an innovation to detect the cause of welding defects using image processing using the YOLO method. Based on testing using the YOLO method, a success value of 92% was obtained.